Gestión contable de los pasivos de la compañía de internet “Swtelecom S.A”, parroquia Barreiro-Babahoyo,2022. - Rivera Quinto, Milena Isabel (2022)
The case study was carried out in the company Swtelecom s.a, which is dedicated to the sale of internet packages. The objective of the investigation was to determine the accounting management of the liabilities of the Internet company. His line of research is Financial, Administrative, Tax, Audit and Control Management, which is related to the Financial Management, Tax and Social Commitment research sub-line. A quantitative methodology with an analytical-descriptive approach was applied, as a technique the documentary analysis was used that corresponds to the review of the results statements of the years studied. It is concluded that the lack of control points and documentation has generated ineffective processes, as well as the lack of control by the company's management, has caused incompatible functions to be carried out. In addition, the analysis carried out on the income statements of the company in the periods studied, corroborated the incident problem of the company, in said analysis it was possible to observe the difference in values that existed between one period and another, caused by expenses of little relevance. , and for the cancellation of taxes, confirming that no pertinent management is carried out in its accounting.